In situ synchrotron study of ordered and disordered LiMn1.5Ni0.5O4 as lithium ion battery positive electrode. (1st September 2016) - Samarasingha, Pushpaka B.; Sottmann, Jonas; Margadonna, Serena; Emerich, Hermann; Nilsen, Ola; Fjellvåg, Helmer
Abstract: In situ powder synchrotron diffraction and X-ray absorption spectroscopy have been used to investigate cation ordered as well as disordered modifications of the LiMn1.5 Ni0.5 O4 spinel-type compound as a Li-ion battery (LIB) cathode during electrochemical cycling. The structural state depends on the adopted heat treatment conditions and is ascertained by Raman and neutron diffraction data. The degree of Mn-Ni ordering (none, partial, complete) is one parameter that influences the electrochemical behaviour. The in situ data reveal significant differences in behaviour with respect to structural phase transitions during electrochemical cycling. Ordered Li2 Mn3 NiO8 ( P4 3 32 ) undergoes two consecutive first order structural phase transitions between spinel type phases during charging - discharging. These are most probably connected with steps in oxidation state for the Ni-atoms as supported by XANES data. The disordered phases ( Fd -3 m ) show a mixed "solid solution - two phase" behaviour accompanied by a smooth decrease in the unit cell volume during charging over the two redox steps involved, Ni 2+ /Ni 3+ /Ni 4+, however, also with volume jumps at first order transitions. This combined behaviour is explained for the first time for spinel type LiMn1.5 Ni0.5 O4 materials. It is not clear why ordered and disordered phases show different phase behaviors depending on the state of (dis)charge. This could be due to higher valent Mn taking part in the redox activity at higher voltages, however, future verification is required. Graphical abstract: